The Exchange Rate Plays a Crucial Role in the Consumer Price Index as it Affects the Inflation - Sari, Lola Fitria; Nawasiah, Nana; Wijaya, Agustinus Miranda (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Purpose: This study aims to analyze the exchange rates and inflation on the Consumer Price Index (CPI) in Indonesia. Fluctuating exchange rates and high inflation are often major concerns in the economy, as both can affect people's purchasing power and overall economic stability. Methodology: The method used in this study is multiple regression analysis, with CPI as the dependent variable, and exchange rates and inflation as independent variables. The data used covers the period 2020 to 2023 obtained from the Central Statistics Agency (BPS) and Bank Indonesia. Finding: The results of the study show that both exchange rates and inflation have a significant effect on CPI. In particular, an increase in the exchange rate tends to increase the price of imported goods, which in turn drives up the CPI. In addition, high inflation contributes to an increase in people's cost of living. Implication: The government needs to maintain exchange rate stability to prevent an increase in the price of imported goods that can affect the CPI. In addition, controlling inflation is key to maintaining people's purchasing power and economic stability. Originality: This study makes a new contribution by analyzing the simultaneous impact of exchange rates and inflation on CPI in Indonesia during the period 2020-2023. Keywords: Consumer Price Index, Exchange Rate, Inflation.